Exploring the Dipteryx alata fruit endocarp as a novel source for the synthesis of silver nanoparticles: antibacterial and photocatalytic insights for water purification - de Morais, Eduardo Beraldo; Nascimento, Marielle Xavier; de Vasconcelos, Leonardo Gomes; Golin, Rossean; Lopes, Paulo Renato Matos [UNESP]; Ambrosio, Jéssica Aparecida Ribeiro; Simioni, Andreza Ribeiro (IWA Publishing, 2024)
A simple, rapid, and non-toxic method was developed to synthesize silver nanoparticles (AgNPs) using an aqueous extract from the endocarp of Dipteryx alata fruit (DAE), a tree species native to the Brazilian Cerrado. The synthesis involved mixing DAE with a solution of AgNO3 (2 mM) at room temperature. AgNPs synthesis was confirmed through detection of the surface plasmon resonance band at 421 nm. Characterization revealed spherical AgNPs with an average diameter of 137.5 + 59.3 nm. FTIR analysis confirmed phytochemical involvement in AgNPs reduction and capping, while XRD analysis indicated their crystalline nature with a face-centered cubic structure. AgNPs exhibited antibacter-ial activity against Escherichia coli and Enterococcus faecalis, with zones of inhibition ranging from 10–4 mm for E. coli and 9–13 mm for E. faecalis, indicating sensitivity to AgNPs. Photocatalytic activity against rhodamine B (RhB) resulted in 99.3% removal in 180 min, with a degradation rate constant of 0.034 L mg-1 min-1 based on pseudo second-order kinetics. Phytotoxicity studies confirmed the non-toxic nature of degraded RhB products on Cucumis sativus. These findings highlight the potential of AgNPs from DAE extract in antibacterial and dye remediation applications.
Keywords: green synthesis; photocatalytic degradation; phytotoxicity; textile dyes; water purification